Archives of Physiotherapy - Baccini, Marco
Archives of Physiotherapy (formerly Italian Journal of Physiotherapy) is an open access journal disseminating research covering all aspects of physiotherapy. Featured topics include clinical trials in different areas of disability (musculoskeletal, neurological, cardio-pulmonary), diagnostic, measurement-focused, observational, prognostic and qualitative studies, as well as systematic reviews, meta-analyses and case reports. The journal also welcomes Letters to the Editor, which provide thoughtful debate on issues of concern to the physiotherapy profession and related disciplines. The publication costs for Archives of Physiotherapy are covered by The Italian Society of Physiotherapy (Società Italiana di Fisioterapia, S.I.F.) and The University of Applied Sciences and Arts of Southern Switzerland (SUPSI).